Práticas corporais de aventura na natureza e educação ambiental: uma unidade didática para o ensino médio - Passos, Yunã Lurie Araújo (Universidade Federal de São Carlos, 2025)
Recognizing the potential of Outdoor Adventure Physical Practices (PCAN) to foster environmental awareness and contribute to the development of a critical and sustainable mindset among students, this dissertation aims to describe and analyze the planning and implementation of a didactic unit focused on PCAN. The unit was carried out with a first-year high school class at a federal public school in Caracaraí, Roraima, Brazil. Adopting a qualitative, applied research approach, the study was structured around a 14-lesson pedagogical intervention, with each session lasting 60 minutes and conducted in both school and natural environments. Data were collected through field notes recorded by the teacher-researcher and analyzed using thematic categories, allowing for reflective interpretation of the experiences. The implementation of the unit revealed stronger student bonds with the environment, growing interest in outdoor physical activities, and the emergence of cooperative and ethical behaviors in peer and territorial interactions. The activities also promoted the integration of interdisciplinary and community knowledge by connecting Physical Education with subjects such as Biology, Philosophy, and Animal Science, resulting in contextualized and meaningful learning. The experience redefined how students perceived Physical Education classes, transforming them into spaces of care, belonging, agency, and environmental reflection. It also led to improvements in the teacher-researcher’s pedagogical practices, particularly in the use of active methodologies, attentive student engagement, and the integration of body, nature, and education. The study concludes that integrating PCAN with Environmental Education in schools is an effective strategy to foster meaningful learning, engage youth, and support the development of critical and responsible attitudes toward today’s socio-environmental challenges.
Outdoor adventure physical practices and environmental education: a didactic unit for high school students
Keywords: Educação física escolar; Práticas corporais de aventura na natureza; Educação ambiental; School physical education; Outdoor adventure physical practices; Environmental education; CIENCIAS DA SAUDE::EDUCACAO FISICA; CIENCIAS HUMANAS::EDUCACAO